Incentives for investment in fast broadband: How much can be expected from the proposed European Code? - J. Scott Marcus; Veronica Bocarova; Georgios Petropoulos (International Telecommunications Society (ITS), 2017)
In September 2016, the European Commission presented legislative proposals to replace the European Regulatory Framework for Electronic Communications (RFEC) with a new European Electronic Communications Code. Among the many stated objectives was to stimulate more rapid investment in fast and ultra-fast broadband. One can argue that the RFEC was put in place in 2002, at a time when networks were not yet liberalised or privatised, and when investment needs of existing copper networks were fairly consistent and predictable. As a consequence, the RFEC put great emphasis on achieving competition, relatively little on achieving investment. This reflects to some extent a preference for optimisation of static efficiency over dynamic efficiency, which was perhaps in order given that the former is far easier to analyse than the latter. In this paper, we review the regulatory instruments that provided in the European Code, and consider based on the economic literature, publicly available statistics, and our own analysis the degree to which the Action Lines in the proposed European Code are likely (individually or collectively) to contribute to increased investment in fast broadband in practice. Our assessment is that the proposed enhancements to broadband policy in the proposed European Code are broadly in the right direction, and collectively are likely to offer network operators a more profitable and predictable business case for investment in high speed broadband. Notwithstanding our observations that the case for FTTP/FTTP can often be significantly overblown, we would still say that this is a welcome or overdue change. The risks implied by insufficient specification of these provisions in the European Code, and the lack of clarity as regards technological neutrality, are however significant. We would hope that these provisions can be sharpened in the course of the legislative process.
Keywords: 330